(untitled) (Journal of actual problems of jurisprudence, 2019)
This article is devoted to the problem of interrogation during the court session and the importance of formation the tactics of public prosecutor in this process and detailed analysis of its peculiarities. To determine the matter of interrogation the author used the judicial statistics, archives, questionnaire and the carried out analysis is summed up.